Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1086/649925
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of a Clinical Prediction Rule for Nosocomial Pneumonia after Coronary Artery Bypass Graft Surgery

Abstract: Using a large cohort of patients treated at community and teaching hospitals, we derived and validated a prediction rule for pneumonia after CABG. This index may prove to be useful in prioritizing receipt of preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 48 publications
9
75
3
3
Order By: Relevance
“…1 Post-operative pneumonia is the most prevalent of all hospital-acquired infections following CAB, and is associated with increased resource utilization, morbidity and mortality. 2 Indeed, patients developing pneumonia following CAB have four-fold increased odds of mortality and three-fold increased length of stay, relative to those patients not developing pneumonia. 2 Nonetheless, accurate and reliable estimation of an individual’s risk of developing pneumonia is hampered by its low relative incidence (~3%).…”
Section: Introductionmentioning
confidence: 99%
“…1 Post-operative pneumonia is the most prevalent of all hospital-acquired infections following CAB, and is associated with increased resource utilization, morbidity and mortality. 2 Indeed, patients developing pneumonia following CAB have four-fold increased odds of mortality and three-fold increased length of stay, relative to those patients not developing pneumonia. 2 Nonetheless, accurate and reliable estimation of an individual’s risk of developing pneumonia is hampered by its low relative incidence (~3%).…”
Section: Introductionmentioning
confidence: 99%
“…In both univariable and multivariable analyses' missing data were coded as the modal value, usually as absence of the symptom. Multivariable analyses were repeated using the chained equations approach to multiple imputation: estimates and Wald P-values 15 based on 50 imputed datasets derived using Rubin's rules. 16 Prediction rules were derived in three stages.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years various attempts have been made to find markers and risk factors to predict the development of nosocomial pneumonia after cardiac surgery. A large cohort study in the USA in 17,145 patients undergoing cardiac surgery was performed to clarify the derivation and validation of postoperative pneumonia [27]. In this study only 361 patients (2%) developed pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to identify thirteen independent predictors for postoperative pneumonia, for example body mass index <18.5, smoking history, creatinine level over 1.2 mg/dl, blood transfusion, mechanical ventilation time >24 hours, cancer history and emergency status. The authors concluded that it may be useful to prove the concept of preventive interventions [27]. However, specificity of this risk model seems to be poor and prevents implementation of preventive strategies.…”
Section: Discussionmentioning
confidence: 99%